The World Food Equation: Interrelations among Development, Employment, and Food Consumption - Mellor, John W.; Johnston, Bruce F. (Journal of Economic Literature, 1984)
The problem of expanding food supply has been made more complex and more dependent on technological progress by the encroachment of a burgeoning population on a limited land area. Rapid growth in the rural labor force in the low-income developing countries not only increases the problem of providing adequate employment, particularly in the face of diminishing scope for expanding the land area, but also reduces the possibility of solving poverty problems simply by a redistribution of assets and income flows. Section II reviews past trends and current levels of food production, trade, and consumption. Section III discusses a controversial issue: the extent and seriousness of food deprivation. These sections lead to the same conclusion: the choice of development strategy is decisive in determining the level at which the food equation balances. An examination of contrasting development strategies and their implications for food production (Section IV) is followed by an exploration of the emerging consensus on the complex and difficult task of implementing a unimodal pattern of accelerated agricultural development, consistent with a high rate of growth in employment and food consumption. Interacting health-, nutrition-, and family-planning programs are viewed as important claimants of organizational and other resources. The review leadsmore » to the conclusion that reduction of malnutrition and related manifestations of poverty requires a set of interacting forces, characterized as a ring, that link nutritional need, generation of effective demand for food on the part of the poor, increased employment, a strategy of development that structures demand towards goods and services that have a high employment content, production of wage goods, and an emphasis on growth in agriculture. 183 references, 4 tables.« less